Optimal knowledge management wisdom management systems concepts and applications - Thierauf, Robert J.; Hoctor, James J.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book outlines a new way of approaching the development and implementation of information systems. Not only does the book explore a different approach to determining an organization's opportunities and solving its problems, but it also highlights methods for optimal decision making"--Provided by publisher.
Section V: The Impact of the Future on Optimal Knowledge Management/Wisdom Management Systems -- 11. Future Developments That Impact Optimal KM/WM Systems -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Knowledge management; Decision making; Electronic books